The diagnostic value of quantitative parameters on dual-layer detector-based spectral CT in identifying ischaemic stroke - Huang, Jian; Chen, Jinghua; Wang, Ximing; Hao, Ling; Zhang, Jinfeng; Zhang, Xiaohui; Sheng, Zhihong; Liu, Kefu (Frontiers in Neurology, 2023)
Objective: To investigate the diagnostic value of quantitative parameters of spectral computed tomography (CT) in ischaemic stroke areas. Methods: The medical records of 57 patients with acute ischaemic stroke (AIS) who underwent one-stop plain computed tomography (CT) head scans, CT angiography (CTA), and CT perfusion (CTP) were retrospectively reviewed. The ischaemic areas (including the core infarct area and penumbra) and nonischaemic areas in each patient were quantitatively analysed using F-STROKE software. Two independent readers measured the corresponding values of the spectroscopic quantitative parameters (effective atomic number [Zeff value], iodine density value, and iodine–no-water value) in the ischaemic area and contralateral normal area alone. The differences in spectroscopic quantitative parameters between the two groups were compared, and their diagnostic efficacy was obtained. Results: The Zeff, iodine–no-water value, and iodine density value all showed significant differences between the ischemic area and non-ischemic tissue (P<0.001). The area under the curve (AUC) of the Zeff value reached 0.869 (cutoff value: 7.385; sensitivity: 93.0%; specificity:70.2%), while the AUC of the iodine density value reached 0.932 (cutoff value: 0.235; sensitivity: 91.2%; specificity: 82.5%), and the AUC of the iodine–no-water value reached 0.922 (cutoff value: 0.205; sensitivity: 96.5%; specificity: 78.9%). Conclusion: The spectral CT quantitative parameters (Zeff, iodine density values, and iodine–no-water values) can effectively distinguish between ischemic and non-ischemic areas in stroke patients.